Gains and Losses of Alternative Food Grains Programmes in Malaysia - Baharumshah, Ahmad Zubaidi (Universiti Putra Malaysia Press, 1994)
This study extends the partial equilibrium analysis to calculate the welfare effects of quotas/tariffs by recognizing the substitution relationship between rice and wheat. It is shown that ignoring the substitution effects leads to a significant understatement of the welfare cost. Three policy options, that is, import quota/tariff, free trade and deficiency payment are considered in this paper. The results show that import quota/tariff is not the most efficient way to support the domestic producers. The net social cost of the rice programme will be lower if the current option is replaced by deficiency payment plans. The social cost under current quota price premium is more than 11 times higher than deficiency payment plan.